Mediasi Customer Engagement Behavior : Digital Marketing dan Kualitas Makanan Guna Mencapai Kepuasan dan Keputusan Pembelian Konsumen - Fahmi, Muhammad; Lesmana, Muhammad Taufik; Prayogi, Muhammad Andi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Purpose– This research aims to understand the mediating role of Customer Engagement in the relationship between digital marketing strategies and Food Quality on the level of consumer satisfaction and purchasing decisions in the Medan City culinary industry.Methodology– This study combines quantitative data analysis and consumer surveys to identify the influence of digital marketing strategies and food quality on consumer behaviour, particularly regarding satisfaction and purchasing decisions. The sample used in this research was 250 culinary consumers in Medan City, and the data analysis technique used Structural Equation Modeling Part Least Square.Findings– The results of this research will provide valuable insight for culinary business owners and marketers in understanding the factors that influence consumer preferences in Medan City.Originality/Novelty– The findings from the research can help culinary business owners develop marketing strategies and improve food quality to meet customer expectations, thereby increasing customer attraction and satisfaction in buying culinary products.Implications–Contribute to a deeper understanding of the complex interactions between digital marketing strategies, food quality, and consumer behaviour in the Medan City culinary industry context.